2018
DOI: 10.13031/jash.12844
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Friction on Actuation Torques of Foldable Rollover Protective Structures

Abstract: Abstract. The number of fatal tractor rollover accidents with an inoperative foldable rollover protective structure (FROPS) has increased sharply in recent years. Operators frequently leave the FROPS in the folded-down position after lowering the FROPS to pass a low overhead obstacle. One possible explanation for leaving the FROPS in the folded position is that raising and lowering the FROPS is a time-consuming and strenuous process. The actuation torques required to raise and lower a FROPS are not well known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Other studies dealt with the analysis of the actuation forces needed to operate foldable rollover protective structures (FROPSs) [97,98], whereas Pessina et al [99] compared the handling load of different narrow-track tractors' FROPSs with the related grasping area. Furthermore, two studies describing field tests aimed at setting a warning device based on the operative conditions of the tractor [100,101] were included in this research stream.…”
Section: Ergonomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies dealt with the analysis of the actuation forces needed to operate foldable rollover protective structures (FROPSs) [97,98], whereas Pessina et al [99] compared the handling load of different narrow-track tractors' FROPSs with the related grasping area. Furthermore, two studies describing field tests aimed at setting a warning device based on the operative conditions of the tractor [100,101] were included in this research stream.…”
Section: Ergonomicsmentioning
confidence: 99%
“…The latter issue was stressed by different studies, shedding light on the necessity of updating technical standards such as the OECD Codes, taking into account the features of modern tractors (e.g., the tractor ballast [120]) and how they are used in practice [65,118]. Similarly, the lack of a clear reference for dynamic tests of ROPS was outlined [117,126], while the inadequacy of the standards related to FROPSs testing (e.g., concerning the grasping area [99] and the actuation torque [97]) needs to be further investigated.…”
mentioning
confidence: 99%
“…Regarding the reasons to leave the FROPS in the folded-down position, Khorsandi, Ayers, Jackson, and Wilkerson (2016) argued that the process of raising the FROPS is time-consuming and strenuous for the operators, also because of the actuation torques required to raise and lower the foldable frame (Khorsandi & Ayers, 2018). A multidimensional study conducted in a group of Italian agricultural operators (Caffaro et al, 2019) showed that handling the FROPS was not associated with a high perceived effort but it was considered by farmers time-consuming and uncomfortable.…”
Section: Introductionmentioning
confidence: 99%